The Thun-Hohenstein album cultures of remembrance in a paper armory - Kirchhoff, Chassica ca. 20./21. Jh (The Boydell Press, 2023)
"The first extensive study of the depiction of the armour in the Thun-Hohenstein Album against the vibrant artistic and cultural contexts that created it."
Zählung aus Liste der bereits erschienenen Bände abgeleitet
Keywords: Thun-Hohenstein Album; Geschichte 1470-1590; Rüstung -- Schutzkleidung, Motiv; Ritter -- Motiv; Zeichnung; Skizzenbuch; Deutschland; Thun'sche Skizzenbuch; Armor / History / Pictorial works; Armor / Early works to 1800; Armor in art